PENGARUH SELF EFFICACY, SIKAP PROFESIONAL DAN DISIPLIN KERJA TERHADAP KINERJA GURU DI SMKN 5 BALIKPAPAN - Rahmawati Imnur; Umi Farida; Diana Pramudya Wardhani (ITB AAS Indonesia Surakarta, 2023)
The purpose of this study was to determine the effect of self-efficacy, professional attitude and work discipline on teacher performance at SMKN 5 Balikpapan. The method used in this research is a quantitative method. The data from this study were obtained from distributing questionnaires to respondents. The number of samples was 46 people taken from the teaching staff at SMKN 5 Balikpapan. The data processing method uses multiple regression analysis. The results showed that the variable self-efficacy (x1) had a significant influence on teacher performance (y) as evidenced by the coefficient of the self-efficacy variable (x1) with a ttest value of 4.390 > ttable 2.021, while the professional attitude variable (x2) had a test value tcount is 3.920 which is greater than ttable 2.021, while the work discipline variable (x3) has a tcount test value of 9.677> 2.021. Based on the f test shows that the probability value is